Peningkatan Pengetahuan Tentang Metode Bermain Aktif Pada Kelompok Guru Untuk Meningkatkan Perkembangan Anak Di Tk Miftahul ‘Ulum Kabupaten Tegal - Harnawati, Riska Arsita; Rahmanindar, Nora; Oktavia, Vivin Avianti (Universitas Nusantara PGRI Kediri, 2021)
One method that can improve children’s development is the active play method. Active play is an activity to get pleasure by involving the limbs. In this activity, children will play an active role by involving various aspect to respond. Apart from parents children can play with teachers at school. Teachers are an important group in the process og child development especially pre-school age, the purpose oh this community servise is to increase teacher knowladge about activity play which is beneficial for the child’s development process. This community servise activity is carried out in 3 stages (coordination with school), the implementation stage (conducting counseling) and the evaluation stage. This activity was carried out at PAUD/TK Miftahul ‘Ulum Tegal Regency. The result of this activity is an increase in teacher knowladge about active play methods in pre-school age children and the hope is that there is a suitability in children and increased development in children, especially pre-shcool age.